2002
DOI: 10.1637/0005-2086(2002)046[0032:ioarfp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Reovirus from Poult Enteritis and Mortality Syndrome and Its Pathogenicity in Turkey Poults

Abstract: Poult enteritis and mortality syndrome (PEMS) is an acute, infectious intestinal disease of turkey poults, characterized by high mortality and 100% morbidity, that decimated the turkey industry in the mid-1990s. The etiology of PEMS is not completely understood. This report describes the testing of various filtrates of fecal material from control and PEMS-affected poults by oral inoculation into poults under experimental conditions, the subsequent isolation of a reovirus, ARV-CU98, from one of the PEMS fecal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…Diseases associated with avian origin reoviruses include viral arthritis/infectious tenosynovitis, malabsorption syndrome, stunting-runting syndrome, and various disorders characterized by pericarditis/myocarditis, chronic respiratory syndrome, nephritis, and multifocal necrotic hepatitis. 1,3,4,[8][9][10][11]21,25,31,38,47,50 Avian reoviruses have also been associated with immunosuppression 24,40 and atrophy of the bursa of Fabricius with characteristic lymphoid depletion and proliferation of connective tissue. 23,24,27,29,36,38,48 Studies in turkeys involving experimental reovirus infection have produced viral arthritis 2,19,30 and poult enteritis, 7,9,20,26,35,42 although descriptions of microscopic lesions caused by turkey-origin reoviruses (TRVs) are limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases associated with avian origin reoviruses include viral arthritis/infectious tenosynovitis, malabsorption syndrome, stunting-runting syndrome, and various disorders characterized by pericarditis/myocarditis, chronic respiratory syndrome, nephritis, and multifocal necrotic hepatitis. 1,3,4,[8][9][10][11]21,25,31,38,47,50 Avian reoviruses have also been associated with immunosuppression 24,40 and atrophy of the bursa of Fabricius with characteristic lymphoid depletion and proliferation of connective tissue. 23,24,27,29,36,38,48 Studies in turkeys involving experimental reovirus infection have produced viral arthritis 2,19,30 and poult enteritis, 7,9,20,26,35,42 although descriptions of microscopic lesions caused by turkey-origin reoviruses (TRVs) are limited.…”
mentioning
confidence: 99%
“…In the more severe forms, runting, immune dysfunction, and mortality occur. 5 Reovirus has been isolated from turkeys with PEMS 9,42 and its milder form, poult enteritis complex. 15,44 Recently, several TRVs collected from commercial turkey flocks affected with poult enteritis were shown to be genetically distinct from previously reported chicken reoviruses.…”
mentioning
confidence: 99%
“…However, Heggen-Peay et al (2002) demonstrated that strain ARV CU98 isolated from PEMS poults does cause some of the clinical signs in PEMS. We aligned published S3 sequences of NC 98, PEMS 85 and TX and designed primers which amplify 460 bp-portion of S3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Carver et al (2001) found flocks with PEMS that were negative for turkey coronavirus. Other viruses that play an important role in the aetiology of PEMS are astroviruses Koci et al 2000) and reoviruses (Simmons et al 2000, Heggen-Peay et al 2002. More recently, PEMS has been described affecting poults in Great Britain, resulting in a first report of this disease there (Culver et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation